Interactions with selected drug renal transporters and transporter-mediated cytotoxicity in antiviral agents from the group of acyclic nucleoside phosphonates - Mandíková, Jana; Volková, Marie; Pávek, Petr; Česnek, Michal; Janeba, Zlatko; Kubíček, Vladimír; Trejtnar, František (Toxicology, 2013)
Members of acyclic nucleoside phosphonates (ANPs) possess antiviral and antiproliferative activities. However, several clinically important ANPs may cause renal injury, most likely due to their active accumulation in the renal tubular cells. The goal of this study was to investigate in vitro relationships between the affinity of several structurally related potent ANPs to selected human transporters and their cytotoxicity. SLC (solute carrier family) transporters (hOAT1, hOCT2, hCNT2, hCNT3) and ABC (ATP-binding cassette) transporters (MDR1, BCRP), which are typically expressed in the kidney, were included in the study. The transport and toxic parameters of the tested compounds were compared to those of two clinically approved ANPs, adefovir and tenofovir. Transport studies with transiently transfected cells were used as the main method in the experiments. Most of the ANPs studied showed the potency to interact with hOAT1. GS-9191, a double prodrug of PMEG, displayed an affinity for hOAT1 comparable with that of adefovir and tenofovir. No significant interaction of the tested ANPs with hOCT2, hCNT2 and hCNT3 was observed. Only GS-9191 was found to be a strong inhibitor for both MDR1 and BCRP. PMEO-DAPy showed the potency to interact with MDR1. Most of the tested substances caused a significant decrease in cellular viability in the cells transfected with hOAT1. Only with the exclusion of GS-9191, a relatively lipophilic compound, did the in vitro cytotoxicity of the ANPs closely correspond to their potential to interact with hOAT1. The increased cytotoxicity of the studied ANPs found in OAT1 transfected cells was effectively reduced by OAT inhibitors probenecid and quercetin. The higher cytotoxicity of the compounds with affinity to hOAT1 proved in the inhibitory experiments evidences that ANPs are not only inhibitors but also substrates of hOAT1. Any clear relationship between the potency of ANPs to inhibit the studied efflux transporters and their cytotoxicity was not demonstrated. In conclusion, the study documented that among the studied transporters hOAT1 seems to be the decisive determinant for renal handling in most of the tested ANPs. This transporter may also play an important role in the mechanism of their potential cytotoxic effects. These facts are in good accordance with previous findings in the clinically used ANPs.
Keywords: Cell Survival; hOCT2; psi; membránové transportní proteiny; RFU; organic anion transporters; DMEM; ABC; Madin–Darby canine kidney II cell line; Humans; HeLa buňky; Dogs; Nephrotoxicity; Organophosphates; hCNT3; OCTs; hCNTs; acyclic nucleoside phosphonates; para-aminohippuric acid; BCRP/ABCG2; HeLa; ledviny; Dulbecco's modified Eagle's medium; human cervical epitheloid carcinoma cell line; CNTs; Kidney; Purines; human organic cation transporter 2; hOAT1; lidé; PAH; Membrane Transport Proteins; zvířata; MDR1; buňky MDCK; MRPs; IC(50); breast cancer resistance protein; organofosfáty; ANPs; MDCK II; human organic anion transporter 1; HeLa Cells; antivirové látky; Madin Darby Canine Kidney Cells; multidrug-resistance proteins; ATP-binding cassette; BCRP; puriny; Antiviral Agents; Transmembrane transport; EMEM; SLC; hCNT2; concentrative nucleoside transporters; human concentrative nucleoside transporter 2; Animals; 1-methyl-4-phenylpyridinium; MPP(+); OATs; human concentrative nucleoside transporter 3; relative fluorescence units; Eagle's minimum essential medium; organic cation transporters; inhibitory concentration to reduce substrate accumulation to 50%; solute carrier family; viabilita buněk